2008
DOI: 10.1007/s00204-008-0336-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of estrogen-induced effects in avian reproduction caused by transovarian application of a xenoestrogen, diethylstilbestrol

Abstract: To clarify breeding failure in avian species caused by the estrogenicity of chemicals, alterations in the reproductive systems of Japanese quail exposed in ovo to a xenoestrogen were investigated. An injection of diethylstilbestrol (DES) into the yolk before incubation decreased, after sexual maturation, egg-laying performance of female quails, which accompanied inducing abnormal development of the oviducts. All females treated with 50 ng DES/g of egg did not lay eggs, while 0.5-5 ng DES/g reduced egg weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
3
14
1
Order By: Relevance
“…A reduction in transcript levels of the CYP11A1 gene in the gonads of male chicks, consistent with our results from in ovo exposure to estrogen analogs [6,21,22], further indicated the estrogenic potency of o,p 0 -dicofol in living organisms. Reduction in concentration of the cholesterol side-chain cleavage enzyme may cause depletion of the precursors of steroid hormones during development, although concentrations of mRNAs for the other enzymes were not markedly altered.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A reduction in transcript levels of the CYP11A1 gene in the gonads of male chicks, consistent with our results from in ovo exposure to estrogen analogs [6,21,22], further indicated the estrogenic potency of o,p 0 -dicofol in living organisms. Reduction in concentration of the cholesterol side-chain cleavage enzyme may cause depletion of the precursors of steroid hormones during development, although concentrations of mRNAs for the other enzymes were not markedly altered.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the impacts of estrogenic compounds on living birds cannot be estimated only from their potential to activate the ER in vitro. We previously reported that the effects on the genital tracts of Japanese quails of in ovo DES treatment prior to incubation markedly differ from treatment at 10 d of incubation [19,21]. Early exposure to DES caused greater disruption to the elongation of both the left and right genital tracts than did later exposure and stunted egg-laying itself, but late exposure caused greater impairment to eggshell formation without greatly damaging egg production.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, injecting pellets of estradiol 3-benzoate subcutaneously in laying hens was reported to increase shell thickness and improve shell deformation (Wistedt et al, 2014). In contrast, an injection of 0.5-5 ng g −1 diethylstilbestrol (DES) into the yolk before incubation decreased later egg weight, shell strength and thickness, which accompanied abnormal development of the oviducts after sexual maturation (Kamata et al, 2009). To date, whether the effect of calcium on shell quality is mediated by estradiol remains unclear despite a potential role of estradiol either in mediating calcium metabolism (Bar et al, 1996) or in regulating the key enzyme involved in the process of shell calcification (Bar et al, 1996;Holm et al, 2001;Berg et al, 2004;Kamata et al, 2009).…”
Section: Discussionmentioning
confidence: 99%